Acute Compartment Syndrome - Cepková, Jana; Ungermann, Leoš; Ehler, Edvard (My University, 2020)
Acute compartment syndrome occurs most frequently in connection with injuries, terminal or chemical damage of tissues, ischemia,the activity of toxins or in patients with tissue ischemia or muscle necrosis. Clinical findings have found pronounced pain, followed by paresthesias, pallor, and paresis. Decreased pulsation of arteries has also been a frequent finding. In severe forms decompressive fasciotomy has been indicated within the first 12–24 hours after diagnosis. In the following paper, the authors present the case report of a 68-year woman who swallowed 1500 mg of trazodone as an attempt at suicide. After 12 hours her husband found her lying on the carpet with compression of the left arm under the trunk. The patient was treated conservatively and followed clinically,examined by ultrasonography, EMG and finally MRI.
Syndrom akutního oddělení‎
Keywords: compartment syndrome; trazodone intoxication; ultrasonography; electromyography; magnetic resonance imaging; syndrom oddělení; ultrasonografie; elektromyografie; magnetická rezonance